The Influence of Emotional Labor on Service Quality with Burnout as a Mediating Variable - Elshafa Salsabil Anwar; Resekiani Mas Bakar; Hilwa Anwar (Badan Penerbit STIEPARI Press, 2025)
The existence of inconsistent nursing practices in realizing quality services causes complaints experienced by both patients and nurses. This inconsistency can be attributed to various factors, two of which are emotional labor and burnout. Emotional labor, specifically deep acting and surface acting, plays a significant role in how nurses regulate their emotions to meet professional expectations, which may impact their perceived service quality. Meanwhile, burnout, characterized by emotional exhaustion, depersonalization, and reduced personal accomplishment, is a psychological response to prolonged work-related stress and is commonly experienced by nurses in high-pressure environments. This study aims to determine the effect of deep acting and surface acting on service quality, with burnout as a mediating variable. The research utilized a quantitative survey design. Respondents consisted of 249 nurses selected through cluster random sampling. Instruments used in this study included the Service Quality Scale, Emotional Labor Scale, and Burnout Scale. Mediation testing was conducted using Hayes' PROCESS macro to analyze the indirect effects. The analysis results showed that burnout significantly mediates the relationship between emotional labor and service quality. Specifically, burnout mediates the effect of deep acting (b = 0.20, 95% CI [0.05–0.37]) and surface acting (b = 0.20, 95% CI [–0.40 to –0.132]) on service quality. These findings indicate that both deep acting and surface acting influence service quality, either directly or through the mediating effect of burnout. Understanding these relationships is crucial for hospital management to develop strategies that reduce burnout and promote effective emotional regulation among nurses. Interventions such as emotional resilience training and supportive work environments may help enhance service quality by managing emotional labor more effectively and reducing the negative impact of burnout.